Deconstructing information literacy discourse: Peeling back the layers in higher education. (December 2021) - Hicks, Alison; Lloyd, Annemaree
The discourses of information literacy practice create epistemological assumptions about how the practice should happen, who should be responsible and under what conditions instruction should be given. This paper employs a discourse analysis method (Potter, 2008) to identify discourses of information literacy and the learner from within higher education focused professional texts. Texts analysed include 4 recent English-language models of information literacy and 16 textbooks. Analysis suggests that within higher education, information literacy is shaped by 2 conflicting narratives. The outward facing narrative positions information literacy as an empowering practice that equips learners with the knowledge and skills that they need within complex and fast-paced information environments. The inward facing narrative positions learners as incompetent or as lacking the ability to operate within higher education. This deficit perception consequently threatens the sustainability of information literacy practice by reframing empowerment as a process of top-down behaviour modification. This paper represents the first in a research programme that interrogates the epistemological premises and discourses of information literacy within higher education.